EXPRESSION AND CHARACTERIZATION OF BOVINE CHYMOSIN IN PICHIA (KOMAGATAELLA) PASTORIS - Akishev , Zh.D.; Abdullayeva , A.N.; Abeldenov, S.K.; Khassenov , B.B. (Eurasian Journal of Applied Biotechnology, 2017)
Bovine chymosin (EC 3.4.23.4), which belongs to a family of aspartic proteases, is mainly derived from mammalian gastric mucosal cells of the abomasum of unweaned calves. Chymosin contains two residues of Asp in an active site, which catalyze the selective cleavage of a peptide bond in κ-casein between Phe105 and Met106. This catalytic process yields insoluble para-κ-casein, which causes milk coagulation. In this study, we sought to identify an alternative milk coagulant that is safe and efficient and, at the same time, can produce cheese with a good taste. Bovine prochymosin B was chosen and constitutively expressed at a high level in Pichia pastoris. The recombinant chymosin protein was expressed as a secretory form and was found to exhibit milk-clotting activity. It was stable at 25–50°C and had optimal activity at 37°C and pH 6.27. The activity of the recombinant chymosin was activated by cations such as Ca2+, Mg2+, Fe3+, Cd2+, Co2+, and Mn2+, but inhibited by Ni2+, and was not affected by Na+, K+, Cs2+, and Li+. These results suggest that recombinant bovine chymosin is an acid milk coagulant, and that it could be a safe and efficient enzyme suitable for use in cheese production.